KINERJA PENYULUH LAPANGAN KELUARGA BERENCANA (PLKB): TANTANGAN DAN SOLUSI DALAM MEMBANGUN KELUARGA YANG BERKUALITAS - Anisah Yafi’ Nur Zahro; Chantyka Nirmala Sari, Niky Kencana Putri, Ummu Kultsum, Praseta Arya Abyansyach, Agustina Tri Wijay (CV. Adiba Aisha Amira, 2025)
This article discusses the role of Family Planning Field Officers (PLKB) in building quality and prosperous families in Godean District, Sleman, Yogyakarta. The family is the smallest unit in society that has a significant influence on national development, especially in the context of sustainable family planning. This research uses qualitative methods by interviewing PLKB to understand the challenges and strategies faced in implementing the Family Planning (KB) program. The research results show that although PLKB plays an important role in education and advocacy, they face various obstacles such as cultural stigma, limited human resources, and lack of facility support. Collaborative efforts with community leaders and increased outreach and education are the keys to overcoming this challenge. Family planning programs have proven effective in reducing birth rates and improving family welfare, thereby supporting sustainable economic growth. This article emphasizes the need for a comprehensive approach and multisectoral cooperation to strengthen the implementation of family planning programs in Indonesia.